Pengaruh Kebijakan Keselamatan, Kesehatan Fisik, Dan Dukungan Psikologis Terhadap Kesejahteraan Pekerja Di Landside Bandar Udara Internasional Zainuddin Abdul Madjid Lombok. - Suci Angriani; Arif Fakhrudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the effect of safety policies, physical health, and psychological support on the well-being of workers in the landside area of ​​Zainuddin Abdul Madjid International Airport, Lombok. Work activities in the landside area have a fairly high level of physical and psychological risks because workers are faced with operational demands, time pressure, and responsibilities for serving passengers. These conditions can affect worker well-being if not supported by the implementation of adequate safety policies, physical health, and psychological support. This study uses a quantitative method with a survey approach. Data collection was carried out by distributing questionnaires to landside workers including security officers, cleaning staff, customer service staff, and operational staff. The data obtained were analyzed using multiple linear regression analysis to determine the influence of each variable partially and simultaneously. The results of the study indicate that safety policies, physical health, and psychological support have a positive and significant influence on worker well-being. Simultaneously, these three variables also make a significant contribution to improving worker well-being in the landside area of ​​Zainuddin Abdul Madjid International Airport, Lombok. This study is expected to be a consideration for airport managers in improving the quality of the work environment, the implementation of occupational safety, physical health, and psychological support to create better worker well-being.